Analisis Pengendalian Internal Kas Berbasis Kerangka COSO pada BUMDes Kalimas - Siti Rizki Khaerunnisa; Ayatulloh Michael Musyaffi; Petrolis Nusa Perdana (LPPM Universitas Negeri Jakarta, 2026)
This study aims to analyze internal cash control at BUMDes Kalimas based on the COSO framework. The study focuses on five components of internal control: control environment, risk assessment, control activities, information and communication, and monitoring activities. This research used a qualitative case study approach. Data were collected through interviews and documentation involving the Head of BUMDes, Treasurer, Supervisor, Village Head, and Village Treasurer selected using purposive sampling. The data were analyzed using thematic analysis. The results show that internal cash control at BUMDes Kalimas has generally been implemented adequately through SOPs, authorization procedures, reconciliation, reporting, and monitoring activities. However, risk assessment has not been conducted systematically, and financial recording is still performed manually, creating potential recording errors Keywords: BUMDes, cash management, COSO, internal control, BUMDes governance.